Response Surface Methodology and Textural Profile Analysis for Optimization of Fruit Peel-Based Extruded Snack (Elbow Macaroni) - Pragya Mishra; Ena Gupta; Karishma Gupta (Journal of Food Quality)
Fruit peel (papaya and banana peel) waste, an agricultural by-product of the fruit processing industry, has abundant phytonutrients and is utilized as a new raw ingredient to develop extruded snack products (macaroni). In our study, macaroni was formulated by response surface methodology (RSM) and textural profile analysis (TPA) using a texture analyzer. The three critical ingredients A = FPB (i.e., papaya and banana peel blend mixed in the ratio of 5 : 2), B= finger millet, and C= semolina were selected to optimize macaroni with balanced nutrition and wholesomeness. Individual 3D plots of the different quality response variables were superimposed, and the maximum sensory scores in terms of texture, colour and appearance (C&A), and overall acceptability (OA) were 5.9, 6.6, and 6.1, respectively. The optimized critical, independent parameters (A = 30.66 g, B = 26.67 g, and C = 12.66 g) were observed for nutritional parameter as energy = 318.3 kcal, protein = 9.6 g/100 g, fiber= 2.7 mg/100 g, and calcium = 26.4 mg/100 g and textural profile (25.1 g force, 0.8 (dimensionless), 22.64 N, 0.91 mm, 20.66 N/mm for hardness/firmness, cohesiveness, gumminess springiness, chewiness, respectively). The proximate composition of optimized fruit peel macaroni was reported to have 5.06, 9.7, 2.7, 1.33, 1.42, and 79.79 percent of moisture, protein, fibre, fat, ash, and carbohydrate, respectively. Thus, instead of disposing and causing environmental hazards, the fruit peels act as promising sources for food supplementation and can be utilized for the nutritional enrichment of snack foods. The present work proposes an alternative method of utilizing food processing wastes (fruit peel) to develop useful value-added extruded food products. Such a replacement in innovative snacks may help in combating malnutrition and reduce the risk of obesity due to overconsumption of snack products.